A Thorough QT/QTc Study With Laquinimod, a Novel Immunomodulator in Development for Multiple Sclerosis and Huntington Disease. Issue 1 (22nd May 2018) - Spiegelstein, Ofer; Mimrod, Dorit; Rabinovich, Laura; Eyal, Eli; Sprenger, Craig; Elgart, Anna; Samara, Emil; Morganroth, Joel
Abstract: In this randomized double‐blind study, 4 groups of healthy subjects (50 per arm) participated to evaluate the effect of laquinimod, an oral treatment in development for multiple sclerosis and Huntington disease, on the QTc interval. Subjects received a dose of either 0.6 or 1.2 mg/day laquinimod for 14 days, placebo for 14 days, or 13 days of placebo followed by a dose of 400 mg moxifloxacin on day 14. Continuous 12‐lead electrocardiograms were recorded on day –1 (baseline) and days 14 to 17, and quadruplicate electrocardiograms were extracted at predefined time points. The primary measure was time‐matched change from baseline in individual QTc (QTcI), and an analysis of variance was conducted on the placebo‐corrected change from baseline data (ddQTcI). Pharmacokinetic‐pharmacodynamic and safety assessments were included. Results showed that the upper limits of the 2‐sided 90%CI for ddQTcI for both laquinimod doses were below 10 millisconds at all time points, whereas lower limits for moxifloxacin were above 5 milliseconds. No notable changes in ECG parameters were observed. Pharmacokinetic/pharmacodynamic analysis showed no positive correlation between laquinimod plasma levels and QTcI. In conclusion, laquinimod was not found to affect cardiac repolarization or to cause prolongation of QTcI at doses of 0.6 and 1.2 mg/day.